2000
DOI: 10.1093/rheumatology/39.5.501
|View full text |Cite
|
Sign up to set email alerts
|

An observer-blinded comparison of supervised and unsupervised aerobic exercise regimens in fibromyalgia

Abstract: This was a 48-week randomized single (observer) blind study in a teaching hospital rheumatology and physiotherapy department. The subjects were 74 patients who fulfilled the American College of Rheumatology criteria for fibromyalgia. Results and conclusions. A 12-week exercise class programme with home exercises demonstrated no benefit over a single physiotherapy session with home exercises in the treatment of pain in patients with fibromyalgia. Neither group (nor the groups combined) showed an improvement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
2
22

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 6 publications
2
53
2
22
Order By: Relevance
“…Em um estudo transversal (40) , interação com outros pacientes com FM também é importante, pois o principal fator relacionado ao nível de atividade física foi ser membro de uma associação de pacientes. Apenas dois estudos foram desenhados para avaliar os determinantes de adesão, mostrando que um programa educacional associado não aumentou a participação regular (15) e que exercícios supervisionados (24) têm maior adesão (72%) do que treino não-supervisionado (50%, p<0.05). Os indivíduos que abandonaram o tratamento foram aqueles que inicialmente tinham piores escores de dor, eram mais estáveis emocionalmente e com maior vitalidade.…”
Section: Valimunclassified
See 1 more Smart Citation
“…Em um estudo transversal (40) , interação com outros pacientes com FM também é importante, pois o principal fator relacionado ao nível de atividade física foi ser membro de uma associação de pacientes. Apenas dois estudos foram desenhados para avaliar os determinantes de adesão, mostrando que um programa educacional associado não aumentou a participação regular (15) e que exercícios supervisionados (24) têm maior adesão (72%) do que treino não-supervisionado (50%, p<0.05). Os indivíduos que abandonaram o tratamento foram aqueles que inicialmente tinham piores escores de dor, eram mais estáveis emocionalmente e com maior vitalidade.…”
Section: Valimunclassified
“…Desses, 12 avaliaram o condicionamento aeróbio (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) , 10 estudaram programas combinados ou associados ao tratamento medicamentoso ou outras intervenções não-farmacológicas (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) . Apenas três envolveram treino de força (28)(29)(30) .…”
Section: Introductionunclassified
“…Aerobic endurance exercises spanning 12 weeks were found to have a positive effect on the fitness and well-being of FMS patients (6). Ramsay et al (46), in contrast, failed to show any superiority of supervised aerobic exercise for 12 weeks over a home exercise program for any parameter except for psychological well-being. A recent review has suggested that supervised aerobic exercise training and strength training may have a beneficial effect on physical capacity and clinical symptoms in FMS patients (47).…”
Section: Discussionmentioning
confidence: 88%
“…There are also some studies related to depression measurements in patients with FMS that yielded conflicting results. In a study carried out by Ramsey et al (46), one group was assigned to perform aerobic exercises and the other group was assigned to perform home exercises for a period of 48 weeks. No amelioration was found in levels of depression, as measured by the BDI scores, either within or between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Significant improvement was observed in pain, physical role, social function and emotional role subscales of SF-36 scale. Favorable effects of regular aerobic activity in FMS patients on pain [2], total myalgia score [3,15], tender point count [14,16], fatigue [15], quality of life [17,18], depression and anxiety [14,19] are reported.…”
Section: Discussionmentioning
confidence: 99%